Lake George and Lake Champlain Paper - The Butler Mine Fire Cut-off - Henry S. Drinker (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1879)
The Butler Mine property is situated in the vicinity of Pittston, in the Wyoming coal-field of Pennsylvania. The coal has been ' worked out from the fourteen-foot or Baltimore vein for a number of years on part of the tract, the old chambers remaining open as when originally abandoned. This vein outcrops on the Butler prop erty, and is nowhere more than sixty feet below the surface of the ground on the line of the cut-off to be described. Above the four teen-foot vein and about, say midway, between it and the surface of the ground, there is another small vein or rider of coal, about twelve inches in thickness. The rock between the two veins is a carbon aceous slate, about twenty-five feet in thickness. Above the smaller vein is a bed of sandstone, varying in thickness, but generally not less than from eight to ten feet. This sandstone is also carbonaceous, but the proportion of carbon is much less than in the slate below. Both rocks have been analyzed, and before the next Institute meet ing, the writer hopes to be able to furnish the exact proportions. The sandstone is overlaid with debris up to the surface of the ground. Some time during the spring of 1876, it was found that the coal left in the worked-out mine had been set on fire, and that the fire was gradually spreading. Inquiry developed the fact that the fire had originally been started by a woman, who had taken up her abode in an old tunnel leading into the workings. Owing to some delay in the early attempts made to extinguish the fire, it finally gained such headway that no ordinary means were found to be effectual. Finally, Mr. C. F. Conrad, civil and mining engineer, of Pittston, Penna., was called in as consulting engineer. He advised the making of a thorough cut through such portion of the old workings as had not been reached by the fire. It was found by survey that this cut could be limited to a length of about one thousand two hundred feet, as the vein faulted on both sides, and that the greatest depth of the cut would be about sixty feet. Subsequently it was decided to tunnel part of the way, thus saving the deepest portion of the cut. In 1856-7, there occurred a fire in the same mine. Two stone walls in V-shape running from the apex of the V towards the out crop, were built to cot the fire 06 and these walls were carried as far as the vein had at that time been worked. After the walls were finished